THE PENGARUH SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN AYAM LOKAL DI PASAR TRADISIONAL KOTA BANDUNG - Febriliani, Rosi Salwa; Herlina, Linda; Yunasaf, Unang (Journal of Social and Economics Research, 2024)
Chicken meat, including that from local chickens, is widely consumed by Indonesians. One of the markets where local chicken is purchased in Bandung City is the Gedebage Traditional Market. The purpose of this study was to analyze the effect of consumer attitudes on purchasing decisions for local chicken at the Gedebage Traditional Market. The research method used is a survey with a quantitative data analysis approach. The research was conducted on March 10 - April 10, 2024, at the Gedebage Traditional Market, Bandung, West Java. Respondents in this study were local chicken buyers who were taken by accidental sampling technique, totaling 97 respondents. The analysis method used is simple linear regression analysis. The results showed that consumer attitudes belonged to the high category with a total percentage of 57.7% and purchasing decisions belonged to the high category with a total percentage of 58.8%. Consumer attitudes have a real influence on purchasing decisions for local chicken, with a regression coefficient value of 0.313. The effect of the independent variable (consumer attitude) on the dependent variable (purchase decision) is 78%, while the remaining 22% is influenced by other variables that are not included in the regression model.